Association between cerebrospinal fluid acidosis and cerebral vasospasm and vacuolation following subarachnoid hemorrhage in a rabbit model - Daltaban, Iskender Samet; Vural, Sevilay; Aydin, Mehmet Dumlu; Gel, Mehmet Selim; Kanat, Ayhan (Frontiers in Neurology, 2025)
IntroductionSubarachnoid hemorrhage (SAH) is a life-threatening neurological emergency often complicated by delayed cerebral vasospasm, a major cause of morbidity and mortality. Clinical observations indicate that cerebrospinal fluid (CSF) acidosis can develop after aneurysmal SAH and may be associated with delayed cerebral ischaemia.MethodsWe examined the relationship between CSF acidosis, vasospasm severity, and vacuolation in a rabbit model of SAH. Twenty-four hybrid rabbits were randomized into control (n = 5), sham-controlled (n = 5), and SAH (n = 14) groups. SAH was induced by injecting autologous blood into the fourth ventricle; sham-controlled animals received saline. CSF samples were collected on days 1, 7, and 14 for pH analysis, and basilar arteries were harvested on day 14 for determination of a vasospasm index (VSI) and vacuole density (VD). To explore the influence of acidosis severity, SAH animals were stratified into mild (CSF pH ≥ 7.20) and severe (CSF pH < 7.20) acidosis subgroups.ResultsCSF pH was significantly lower in the SAH group than in control or sham-controlled animals (overall mean 7.22 ± 0.03 vs. 7.35 ± 0.02 and 7.31 ± 0.01; p < 0.05). While overall VSI did not differ among the groups, animals with severe acidosis displayed a markedly higher VSI than those with mild acidosis (2.83 ± 0.49 vs. 1.60 ± 0.64; p = 0.041). VD was elevated in both sham-controlled and SAH groups compared with controls (p = 0.009 and p = 0.002). Increased vacuolation in sham-controlled animals suggests that surgical manipulation alone can promote vacuole formation. There was a strong inverse correlation between CSF pH and VD (r = −0.75, p < 0.001), whereas no correlation was found between VSI and VD.DiscussionCSF acidosis, vacuolation, and vasospasm severity appear to be interconnected factors in the pathophysiology of SAH. CSF acidosis may contribute to vacuolation and, when profound, to vasospasm severity. However, vacuolation and vasospasm represent distinct pathological processes.